The General Election Supervisory Agency’s Policy in Conflict Resolution (Case Study: 2019 Legislative Election in North Musi Rawas District) - Eva Kurnia Farhan; Budi Setiyono; Teguh Yuwono; Reni Shinta Dewi (Jurnal Studi Pemerintahan, 2023)
The aims of this research are to identify the Policy of general election super- vision agency (refers as Bawaslu) in conflict resolution in North Musi Rawas District. The success of the election in Indonesia is largely decided by the Election Supervisor’s work as a supervisory entity that controls the stages of conducting regional elections. The approach method used in this study is the normative juridical approach method. Qualitative approach method with theo- retical approach related to this research. The policy of the Supervisor of Elec- tions in North Musi Rawas Regency is worth reviewing. This study focuses on the supervisory policy established by Bawaslu in legal documents, as well as the lack of Standard Operating Procedures (SOPs) and Human Resources, particularly in the recruitment of Bawaslu members. The findings of this research is strengthens the democratic constitutional system, ensures fair and transparent elections, ensure consistency of electoral system arrangements, provide legal certainty and avoid duplication in election arrangements; and ensures effective and efficient elections.